Language Anxiety among Jordanian EFL Learners during Public Speaking - Abdullah Alsaleem, Alaa; Hilmi Hamzah, Mohd (Journal of Applied Research and Multidisciplinary Studies, 2023)
The current research attempted to explore how Jordanian EFL learners perceive their English public speaking anxiety. The study applied qualitative methodology via interviews. The research subjects comprised of six Jordanian postgraduate EFL learners (PhD students) selected from four public universities in Malaysia. The findings illustrated that the attitudes and motivation of Jordanian EFL learners play an important role in determining their English public speaking anxiety. More precisely, attitude and motivation negatively influenced Jordanians’ English public speaking anxiety.